Cleogonus insulcatus Fiedler, 1954 (Coleoptera: Curculionidae): first report in Brazil and a new host plant record, Handroanthus impetiginosus (Mart. ex DC.) Mattos - Marcelo T Castro; Sandro C.L. Montalvão; Germano H. Rosado-Neto; Rose G. Monnerat (Entomological Communications, 2020)
The purple trumpet tree [Handroanthus impetiginosus (Mart. Ex DC.) Mattos - Bignoniaceae] is one of the most prominent tree species in the Brazilian Federal District, with more than 150 trees in the Plano Piloto region of Brasília. In March 2017, weevils (Coleoptera) were observed in ripe fruits of purple trumpet trees feeding on already dried seeds. The objective of this paper is to report and describe the main damage to seeds and pods of H. impetiginosus in Brasília, Brazil, caused by this beetle. The insect was identified as Cleogonus insulcatus Fiedler, 1954 (Coleoptera: Curculionidae). Of the 126 fruits analyzed, 104 exhibited predation by C. insulcatus (82.5%) and 377 larvae were collected inside the pods feeding on the seeds. This is the first report of C. insulcatus in Brazil and the first record of damage to H. impetiginosus pods and seeds caused by this insect.